2012
DOI: 10.1111/j.1462-2920.2012.02877.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of predation and competition on the survival of commensal and pathogenic fecal bacteria in aquatic habitats

Abstract: The role of fecal indicator bacteria (FIB) in water quality assessment is to provide a warning of the increased risk of pathogen presence. An effective surrogate for waterborne pathogens would have similar survival characteristics in aquatic environments. Although the effect of abiotic factors such as sunlight and salinity on the survival of FIB and pathogens are becoming better understood, the effect of the indigenous microbiota is not well characterized. The influence of biotic factors on the survival of non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
68
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 54 publications
8
68
0
Order By: Relevance
“…This is not surprising, as osmotic stress posed by the elevated salinity of the marine environment is a known stressor for E. coli cells (54,55). When indigenous microbiota were present, E. coli decay in the water column was significantly greater than that in the disinfected controls, and this trend was evident in both water types, a finding consistent with other studies (43,(56)(57)(58). Although less pronounced, the same pattern of extended E. coli persistence in disinfected mesocosms compared to natural mesocosms continued for sediments in both water types.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is not surprising, as osmotic stress posed by the elevated salinity of the marine environment is a known stressor for E. coli cells (54,55). When indigenous microbiota were present, E. coli decay in the water column was significantly greater than that in the disinfected controls, and this trend was evident in both water types, a finding consistent with other studies (43,(56)(57)(58). Although less pronounced, the same pattern of extended E. coli persistence in disinfected mesocosms compared to natural mesocosms continued for sediments in both water types.…”
Section: Discussionsupporting
confidence: 80%
“…Maintenance of elevated FIB concentrations in sediments is of practical importance and has public health implications, as previous studies indicated that resuspension can lead to increased bacterial concentrations in the water column (76)(77)(78)(79)(80)(81)(82). A recent study (43), which manipulated indigenous microbiota by adding kanamycin to reduce competition from prokaryotic community, found that inclusion of the antibiotic extended E. coli survival in the river water and sediments, corroborating our results.…”
Section: Discussionsupporting
confidence: 80%
“…The increases in bacterial concentrations observed in sediments for these targets are most likely from replication, as the balance calculations show that the increases in sediment cannot be accounted for simply by losses from the water column. Sediments offer protection from UV light inactivation, predation, and nutrient deprivation by attachment of the bacteria to sediment particles (13,14,65) and seem to provide a habitat for growth under these experimental conditions. Although an exponential decay model (such as DMFit) could be used to calculate decay rates of bacteria in the water columns of freshwater and marine water microcosms, the fit of the model to the data was poor in sediments.…”
Section: Discussionmentioning
confidence: 99%
“…A body of literature has established that fecal coliforms, E. coli, and Enterococcus spp. can persist in environmental waters and in sediments (12)(13)(14), indicating the existence of extraintestinal reservoirs of FIB. The ability of enteric pathogens to persist in environmental waters and sediments is much less clear and almost certainly varies by pathogen type and species (13,15).…”
mentioning
confidence: 99%
“…Currently, it is known that populations of microorganisms are the key components in the biogeochemical cycle of organic matter to maintain a balance in natural ecosystems [3]. Various abiotic and biotic factors influence microbiological consortium that directly affect the quality of waste water [4].…”
Section: Introductionmentioning
confidence: 99%